2020
DOI: 10.3390/genes11010098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Sizes of PPARγ rs1801282, FTO rs9939609, and MC4R rs2229616 Variants on Type 2 Diabetes Mellitus Risk among the Western Saudi Population: A Cross-Sectional Prospective Study

Abstract: Type 2 diabetes mellitus (T2DM) is a common polygenic disease with associated comorbidities. Obesity is a major risk factor for the development of T2DM. The aim of this study is to determine the allele and genotype frequency of peroxisome proliferator-activated receptor-γ (PPARγ) rs1801282, fat mass and obesity-associated protein (FTO) rs9939609, and melanocortin 4 receptor (MC4R) rs2229616 polymorphisms and their association with risk of T2DM in the western Saudi population as mediators of adiposity phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
(68 reference statements)
2
12
0
2
Order By: Relevance
“…1 Saudi Arabia is considered one of the top ten countries characterized by a high incidence of diabetes. 2 Accumulating evidence, including previous studies in this region, [3][4][5] indicated that environmental and genetic risk factors play essential roles in T2DM etiopathology. 6,7 One of these factors is oxidative stress, which has been implicated in insulin resistance, ß-cell dysfunction, and impaired glucose tolerance progressing to T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…1 Saudi Arabia is considered one of the top ten countries characterized by a high incidence of diabetes. 2 Accumulating evidence, including previous studies in this region, [3][4][5] indicated that environmental and genetic risk factors play essential roles in T2DM etiopathology. 6,7 One of these factors is oxidative stress, which has been implicated in insulin resistance, ß-cell dysfunction, and impaired glucose tolerance progressing to T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the POMC polymorphism rs934778 has been reported as a risk factor that affects insulin sensitivity [ 15 ]. The rs6232 polymorphism of the gene that codes for PCSK1 has also been associated with both childhood and adult obesity [ 16 ]; likewise, the rs2229616 polymorphism of the MC4R gene has been associated with an increased risk of developing type 2 diabetes mellitus in Saudi patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been few population-based prospective studies reporting RR or HR of T2D. An hospital-based prospective study (n = 738) in Western Saudi population showed no significant association of the FTO-rs9939609 polymorphism with T2D (RR = 1.07, P = 0.190) as an independent variable, whereas the combined genotypes of A/A for FTO rs9939609, C/C for PPAR rs1801282, and C/C for MC4R rs2229616 significantly increased the risk of T2D by 1.82, p = 0.045 (Bakhashab et al 2020). Another longitudinal study (median follow-up of 5.9 years) reported no involvement of the FTO-rs9939609 polymorphism in T2D risk in postmenopausal women including White (n = 1972), Black (n = 1098), Hispanic (n = 456), and Asian/Pacific Islanders (n = 294) in the USA (Song et al 2008).…”
Section: Discussionmentioning
confidence: 95%